STRATEGI KOMUNIKASI BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) PROVINSI RIAU DALAM MENCEGAH KEBAKARAN HUTAN DAN LAHAN DI RIAU - Novella Wulia Saqinah; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Forest fires and land that often occurs in the province of Riau, Riau Province because it is one of the areas that have the largest peat in Indonesia. Land and forest fires occur in the dry season caused by natural factors or non nature, however 99% are caused by the behavior of a human hand that intentionally opening land by burning. Badan Penanggulangan Bencana Daerah (BPBD) province of Riau were present in order to cope with the disaster, one of which is land and forest fires. Course related this Badan Penanggulangan Bencana Daerah (BPBD) region of Riau Province requires a strategy for tackling and preventing the occurrence of forest fires and land in Riau. The purpose of this research is to know the communication strategy of the Badan Penanggulangan Beencana Daerah (BPBD) of Riau Province in preventing forest fires and land in Riau. This research uses qualitative descriptive method. The technique of determining the subject using a purposive technique. Informants in this study is Kabid Prevention and preparedness, the head of the Sub fields of prevention, the head of the Sub areas of preparedness, one person Staffs the field of Prevention and preparedness, and two fields of Information and communication. Data collection techniques were interviews, observation, and documentation. Interactive data analysis techniques Miles and Huberman. To achieve the validity of the data in this study, the authors used an extension of participation and triangulation.Based on the results of the research are already writers do then obtained the results of research to identify issues that the first result is a strategy determining communicators in preventing forest fires and land are the people (employees) BPBD views in terms of his credibility, well rounded, has the experience, the training and has the certificate. Second, to determine the target audience is all society Riau Province especially people who live in areas prone to fires. Third, there are three types of messages i.e. the message informative, persuasive message and a message threatening. The last election strategy there is a media website, social media in the form of facebook and instagram and outdoor media in the form of banners, billboards and brochures. Keyword: Communication Strategy, Badan Penanggulangan Bencana Daerah (BPBD) of Riau Province, Forest and land fires.